Perilaku Aparatur Dalam Pelayanan Administrasi Kependudukan di Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Sidrap - Andi Siti Nursiana (GOVERNMENT : Jurnal Ilmu Pemerintahan, 2025)
A service is considered satisfactory when it is able to meet the needs and expectations of its users. If users are dissatisfied with the services provided, the service can be regarded as ineffective and inefficient. Bureaucratic behavior serves as a key indicator of the effectiveness of public service delivery and represents one of the most visible measures of government performance. Citizens can directly assess government performance through the services they receive, either directly or indirectly. High-quality public services require not only adequate systems and procedures but also positive attitudes and behavior from government officials as service providers. Therefore, government officials need ethical principles as a foundation and guideline in carrying out their duties. Government ethics are intended for public officials who are required to uphold values and moral standards in accordance with their responsibilities and functions. This study employed a qualitative descriptive research method. The research utilized both primary and secondary data sources. Data were collected through observation, interviews, documentation, and literature review. The findings indicate that the behavior of public officials in providing population administration services, as assessed through the dimensions of bureaucratic behavior, has been implemented effectively. Government officials have generally demonstrated responsible conduct, discipline, responsiveness, and professionalism in delivering population administration services, thereby contributing to improved service quality and public satisfaction.